TREATMENT FOR NEURODERMATITIS – BASED ON PATHOGENESIS OF IT (RETROSPEKTIF STUDY) - Sukmawati Tansil Tan; Yohanes Firmansyah; Yurike Indah Pratiwi (Perhimpunan Kesehatan Holistik Indonesia, 2021)
Background: Neurodermatitis is a chronic condition with a high recurrence rate. It is critical to avoid repetitive scratching. As topical treatments for neurodermatitis: topical steroids, intralesional steroids, keratolytic agents, and many more are all available. Menthol, camphora, and Liquor Carbonis Detergent can be used in conjunction with topical steroids to enhance their therapeutic effect. The purpose of this journal is to compare the therapeutic efficacy of combination drugs containing 0.05% clobetasol, 3% liquor carbonis detergent, and 2% salicylic acid to standard therapy for neurodermatitis. Method: This study compares the efficacy of a new treatment therapy utilizing a combination of 0.05 percent Clobetasol, 3% liquor carbonis detergent, and 2% salicylic acid to standard therapy, specifically 0.05 percent Clobetasol. This is a retrospective cohort study conducted at the Indra Clinic. The samples for this study were all cases of neurodermatitis of the skin diagnosed at Indra's clinic between 2016 and 2017. The study's independent variable was the formulation of the drug, while the dependent variable was clinical improvement and the occurrence of side effects. Results: The cure rate for the 126 respondents who received the combination formulation was 88,9%, compared to 77,5%for the 111 respondents who received standard therapy containing 0.05 percent Clobetasol (p : 0,029). Conclusion: The innovative therapy of a 0.05% clobetasol mixture with 3% liquor carbonis detergent and 2% salicylic acid has been shown to improve clinical outcomes in patients with neurodermatitis more than the 0.05% clobetasol standard therapy.